SeMet alleviates AFB1-induced oxidative stress and apoptosis in rabbit kidney by regulating Nrf2//Keap1/NQO1 and PI3K/AKT signaling pathways - Yumei Liu; Jianing Wang; Zhaoyang Chang; Shuangjun Li; Zhikai Zhang; Shiyang Liu; Shuaishuai Wang; Lan Wei; Qiongxia Lv; Ke Ding; Ziqiang Zhang (Ecotoxicology and Environmental Safety, 2024)
The purpose of this study was to explore the protective effect of SeMet on renal injury induced by AFB1 in rabbits and its molecular mechanism. Forty rabbits of 35 days old were randomly divided into control group, AFB1 group (0.3 mg AFB1/kg b.w), 0.2 mg/kg Se + AFB1 group (0.3 mg AFB1/kg b.w + 0.2 mg SeMet/kg feed) and 0.4 mg/kg Se + AFB1 group (0.3 mg AFB1/kg b.w + 0.4 mg SeMet/kg feed). The SeMet treatment group was fed different doses of SeMet diets every day for 21 days. On the 17–21 day, the AFB1 treatment group, the 0.2 mg/kg Se + AFB1 group and the 0.4 mg/kg Se + AFB1 group were administered 0.3 mg AFB1 /kg b.w by gavage (dissolved in 0.5 ml olive oil) respectively. The results showed that AFB1 poisoning resulted in the changes of renal structure, the increase of renal coefficient and serum biochemical indexes, the ascent of ROS and MDA levels, the descent of antioxidant enzyme activity, and the significant down-regulation of Nrf2, HO-1 and NQO1. Besides, AFB1 poisoning increased the number of renal apoptotic cells, rised the levels of PTEN, Bax, Caspase-3 and Caspase-9, and decreased the levels of PI3K, AKT, p-AKT and Bcl-2. In summary, SeMet was added to alleviate the oxidative stress injury and apoptosis of kidney induced by AFB1, and the effect of 0.2 mg/kg Se + AFB1 is better than 0.4 mg/kg Se + AFB1.